2019
DOI: 10.1111/jcmm.14719
|View full text |Cite
|
Sign up to set email alerts
|

Systematic construction and validation of an immune prognostic model for lung adenocarcinoma

Abstract: Lung adenocarcinoma (LUAD), the most common non-small-cell lung cancer, is characterized by a dense lymphocytic infiltrate, which indicates that the immune system plays an active role in the development and growth of this cancer. However, no investigations to date have proposed robust models for predicting survival outcome for patients with LUAD in terms of tumour immunology. A total of 761 LUAD patients were included in this study, in which the database of The Cancer Genome Atlas (TCGA) was utilized for disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 63 publications
(176 reference statements)
1
46
0
Order By: Relevance
“…Different models for predicting the prognosis of lung adenocarcinoma have been developed, based on the tumor microenvironment (Yue et al, 2019), TP53 mutation (Long et al, 2019), and tumor immunology (Luo et al, 2019). However, to our knowledge, in lung adenocarcinoma, no signature based on hypoxia-associated genes has been constructed yet.…”
Section: Introductionmentioning
confidence: 99%
“…Different models for predicting the prognosis of lung adenocarcinoma have been developed, based on the tumor microenvironment (Yue et al, 2019), TP53 mutation (Long et al, 2019), and tumor immunology (Luo et al, 2019). However, to our knowledge, in lung adenocarcinoma, no signature based on hypoxia-associated genes has been constructed yet.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal regulation of cell division and the mitotic cell cycle are key to the occurrence of cancer [25]. Moreover, many studies have shown that metabolic pathways play an important role in HCC [26,27]. In this ceRNA network, we found that 30 lncRNAs may regulate the expression of 75 mRNAs by competitively binding 16 miRNAs.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, our results also revealed that, the in ltration levels of macrophages, DCs, B cells, CD8+ T cells, CD4+ T cells and neutrophils were signi cantly positively correlated with ANLN expression in HCC. A recent study has recognized ANLN as an immune-related gene for lung adenocarcinoma [22]. Although few reports are available to examine the effect of ANLN on the immune microenvironment of HCC, our research provides novel clues for understanding the role of ANLN in HCC.…”
Section: Discussionmentioning
confidence: 86%